2020
DOI: 10.1002/jcsm.12581
|View full text |Cite
|
Sign up to set email alerts
|

A potential therapeutic effect of catalpol in Duchenne muscular dystrophy revealed by binding with TAK1

Abstract: Background Duchenne muscular dystrophy (DMD) is a progressive muscle disease caused by the loss of dystrophin, which results in inflammation, fibrosis, and the inhibition of myoblast differentiation in skeletal muscle. Catalpol, an iridoid glycoside, improves skeletal muscle function by enhancing myogenesis; it has potential to treat DMD. We demonstrate the positive effects of catalpol in dystrophic skeletal muscle. Methods mdx (loss of dystrophin) mice (n = 18 per group) were treated with catalpol (200 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…A recent study reported that TGF‐β1 induced the transdifferentiation of myoblasts into fibroblasts 49 . Similarly, in our previous study, TAK1 activation induced transdifferentiation of myoblasts into fibroblasts 50 . In addition, TAK1 was activated by TGF‐β1, IL‐1β, and TNF‐α in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A recent study reported that TGF‐β1 induced the transdifferentiation of myoblasts into fibroblasts 49 . Similarly, in our previous study, TAK1 activation induced transdifferentiation of myoblasts into fibroblasts 50 . In addition, TAK1 was activated by TGF‐β1, IL‐1β, and TNF‐α in this study.…”
Section: Discussionsupporting
confidence: 89%
“…To specifically knock down TAK1 in skeletal muscles, the AAV‐shRNA‐control and AAV‐shRNA‐TAK1 were intramuscularly injected into the right and left TA muscles, respectively, of mdx and control mice. We found that TAK1 inhibition improved myoblast differentiation and alleviated fibrosis in mdx mice 50 . In addition, we found that p38‐MAPK and MAP 4K2 were activated in the skeletal muscle of mdx mice, while AAV‐shTAK1 and NG25 did not affect MAP 4K2 expression in mdx mice ( Figure S7B and S7C).…”
Section: Discussionmentioning
confidence: 76%
“…More recently, we have shown that cardiac function in the mdx mouse is also improved by simvastatin, due in part to the prevention of fibrosis [3]. In strong support of our findings, two recent studies have independently validated our results by showing positive effects of simvastatin treatment in mdx mice [4,5]. In one of these studies, significant improvements in muscle function (force and fatigue resistance), as well as reduced inflammation, fibrosis and plasma CK were comparable to those in our original paper [5].…”
supporting
confidence: 86%
“…Growing evidence supports the role of TAK1 as a significant regulator of TGFb signaling through the regulation of the profibrotic response in several systems [43][44][45][83][84][85][86][87]. Very recently, it has been shown that the action of Catalpol (an anti-inflammatory and antioxidant drug from Chinese medicinal herb Rehmannia) on DMD histopathology was due to its binding to TAK1 [88,89]. Besides its role in fibrosis, TAK1 also has been described as an important mediator of carcinogenesis and cell survival [90].…”
Section: Discussionmentioning
confidence: 99%